Content of polyphenols and antioxidant activity of extracts from certain species of seaweeds - Natalia M. Aminina; Tatiana I. Vishnevskaya; Ekaterina P. Karaulova; Eugene V. Yakush (Известия ТИНРО)
Polyphenol compounds in extracts from the seaweeds Saccharinа japonica , Fucus evanescens , and Ahnfeltia tobuchinensis are investigated and antioxidant activity of the extracts is evaluated. The extracts were prepared using different solvents (distilled water, ethanol, acetone) or mixtures of the solvents under various conditions. By the species, the polyphenols were extracted better by water from S. japonica and A. tobuchinensis and by 1 : 1 mixture of water and ethanol from F. evanescens . Heating increased the degree of polyphenols extraction but could decrease antioxidant activity of the extracts. After 24 hours extraction by 70 % acetone solution under 50оC, the antioxidant activity of the extract from S. japonica was in 3 times lower as compared with the extract obtained at room temperature, though the polyphenols concentration was almost the same (0.09 and 0.11 mg/mL, respectively). The polyphenols concentration was the highest and antioxidant activity was the strongest for the extract from F. evanescens by 50 % ethanol solution under room temperature. The properties of the extracts from seaweeds are compared with the extracts from terrestrial plants. The polyphenols content in the extract from blackcurrant berry is comparable with the extract from S. japonica and its antioxidant activity is close to that for the extract from F. evanescens .